In-hospital trends of non-communicable disease mortality during the pandemic for patients without COVID-19 at a regional referral hospital in southwestern Uganda - Peter K. Olds; Edwin Nuwagira; Paul S. Obwoya; Grace Kansiime; Nicholas Musinguz; Lenus Tumwekwatse; Racheal Ninsiima; Shadia Mwesigwa; Daniel Mujuni; Ronald Awani Okii; Lorna Atimango; Julius Ssempiira; et al. (BMC Global and Public Health, 2025)
Background: Non-communicable diseases (NCDs) represent a growing health burden in sub-Saharan Africa, especially in Uganda. The COVID-19 pandemic presented significant challenges for the Ugandan healthcare system, though changes in hospital admissions and outcomes for adults with NCDs and without COVID-19 infection remain unknown. We evaluated trends of NCD-related in-hospital mortality among patients without COVID-19 in a large regional referral hospital in Uganda from March 2019 through August 2021. Methods: Between March 1, 2019, and August 31, 2021, we conducted a chart review of Ugandan adults who carried a history of or were admitted for an NCD to Mbarara Regional Referral Hospital. Based on mortality trends, we broke admissions into three periods: Pre-Pandemic (March 1, 2019, to May 31, 2020), Early Pandemic (June 1, 2020, to March 31, 2021), and Late Pandemic (April 1, 2021, to August 31, 2021), and calculated admission and mortality rates for the most common NCD diagnoses. A multivariable logistic regression model was fitted for a primary outcome of in-hospital mortality. Results: Of 3777 total individuals, 1655 were admitted Pre-Pandemic, 1423 in the Early Pandemic, and 699 in the Late Pandemic. We found a five-fold increase in mortality in the Early Pandemic period compared to the Pre-Pandemic and Late Pandemic periods (15.4 vs 2.9 vs 2.4, p < 0.001). Factors associated with increased odds for in-hospital mortality included admission during the Early Pandemic period (odds ratio [OR] 5.59; 95% CI 3.90, 8.02; p < 0.001), admission with hypotension (OR 2.13; 95% CI 1.40, 3.24; p < 0.001), admission diagnosis of malignancy (OR 1.79; 95% CI 1.06, 3.01; p = 0.028) and stroke (OR 1.75; 95% CI 1.06, 2.88; p = 0.028), and each unit increase in SOFA score (OR 1.41; 95% CI 1.30, 1.52; p < 0.001). Length of stay greater than 7 days was associated with decreased odds of in-hospital mortality (OR 0.56; 95%CI 0.40, 0.79; p = 0.001). Conclusions: NCD-associated in-hospital mortality was high in the early COVID-19 pandemic period. Disruptions in longitudinal NCD care that occurred due to the pandemic may have been contributory, though this requires further investigation. Future work should focus on NCD care for hospitalized individuals in resource limited settings and developing more resilient systems of NCD care.
Keywords: Non-communicable disease; Uganda; COVID-19 pandemic; Hospital care